THE ANALYSIS OF THE INDICATORS WHICH REFLECT THE ABILITY OF COMPANIES OF FACING SHORT TERM OBLIGATIONS AND MEDIUM AND LONG TERM MATURITIES - LĂPĂDUŞI MIHAELA LOREDANA; CĂRUNTU CONSTANTIN (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2012)
The company’s solvency and liquidity are two indicators of managing the financial stability, indicators whose management is reflected in a decisive manner on the company results. These are two basic requirements in achieving the financial stability of the company. If liquidity reflects the company's ability to meet short-term obligations, solvency reflects company's ability to meet the medium and long term maturities. One of the most important premises which determine the effective development of a company refers to the action of providing liquidity and solvency. These are the key indicators of financial stability management. Ensuring the solvency is the priority objective of a company that wants to maintain a financial autonomy and the flexibility of management resulting from the balance between revenues and cash flow payments. Liquidity represents the indicator that reflects the quality of the company's financial balance on short-term and measures the ability of the company to meet short-term obligations through rapid transformation of current assets into cash. The purpose of the research includes studying and analyzing the liquidity and solvency of the company whose scope should be reflected in achieving the optimal coefficients of the two indicators. Liquidity and solvency analysis is done by the system of rates that actually reflect those indicators that highlight whether a company has availability to meet short-term maturities or if the size of debt and financial costs allows the company to meet the medium and long term maturities.